Simultaneous Determination of Antibodies to Pertussis Toxin and Adenylate Cyclase Toxin Improves Serological Diagnosis of Pertussis - Knuutila Aapo; Barkoff Alex M; Mertsola Jussi; Osicka Radim; Sebo Peter; He Qiushui (MDPI, 2025)
Serological diagnosis of pertussis is mainly based on anti-pertussis toxin (PT) IgG antibodies. Since PT is included in all acellular vaccines (ACV), serological assays do not differentiate antibodies induced by ACVs and infection. Adenylate cyclase toxin (ACT) is not included in the ACVs, which makes it a promising candidate for pertussis serology with the specific aim of separating infection- and ACV-induced antibodies. A multiplex lateral flow test with PT and ACT antigens was developed to measure serum antibodies from pertussis-seropositive patients (n = 46), healthy controls (n = 102), and subjects who received a booster dose of ACV containing PT, filamentous hemagglutinin, and pertactin (n = 67) with paired sera collected before and one month after the vaccination. If the diagnosis was solely based on anti-PT antibodies, 98.5-44.8% specificity (before and after vaccination, respectively) and 78.2% sensitivity were achieved, whereas if ACT was used in combination with PT, the sensitivity of the assay increased to 91.3% without compromising specificity. No increase in the level of anti-ACT antibodies was found after vaccination. This exploratory study indicates that the use of ACT for serology would be beneficial in combination with a lower quantitative cutoff for anti-PT antibodies, and particularly in children and adolescents who frequently receive booster vaccinations.